Effect of Bevel Angle and Welding Current on T-Joint Using Gas Metal Arc Welding (GMAW) - Zakaria, Z.A. (2019)
In this study, the effects of various welding parameters on welding strength in mild steel A36, welded by gas metal arc welding with fillet joint under 1F position were investigated. The welding current and the angle of bevel are the variable parameters, while welding speed was chosen as constant parameter. Each specimenâs mechanical properties have been measured after the welding process, and the effects of the welding parameters on the strength were investigated. Then, the relationship between welding parameter and mechanical properties is determined. The project used 8 specimens to be studied and to find the best welding parameters for mild steel plate on fillet joint (1F position). Based on the mechanical tests performed, the best welding parameters for the mild steel plate thickness of 5 mm T-joint fillet welds are obtained; it was 120 A for weld current with no bevel angle. Â© 2019, Springer Nature Singapore Pte Ltd.